2019
DOI: 10.1159/000497103
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroabietic Acid Induces Regeneration of Collagen Fibers in Ultraviolet B-Irradiated Human Dermal Fibroblasts and Skin Equivalents

Abstract: Background/Aims: Dehydroabietic acid (DAA) is a natural phytochemical found in red pine trees and herbal plants. While DAA and its derivatives are known for improving diabetes and hyperlipidemia, the antiaging effect and its underlying mechanisms of DAA on skin have not been fully examined. Here, we assessed the antiaging effects of DAA on human dermal fibroblasts and skin equivalents. Methods: We investigated the effect of DAA on the secretion of type I procollagen and matrix metalloproteinase-1 (MMP-1) in ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…UVB radiation induces MMP-1 gene transcription by triggering the MAPK signaling pathway via the phosphorylation of JNK, ERK, and p38 signaling cascades [3]. In the NHDF cells used in this study, we confirmed that UVB induced JNK, ERK, and p38 phosphorylation in a time dependent manner.…”
Section: Sarmentosamide (1) Downregulates Jnk and Erk Phosphorylationsupporting
confidence: 79%
See 2 more Smart Citations
“…UVB radiation induces MMP-1 gene transcription by triggering the MAPK signaling pathway via the phosphorylation of JNK, ERK, and p38 signaling cascades [3]. In the NHDF cells used in this study, we confirmed that UVB induced JNK, ERK, and p38 phosphorylation in a time dependent manner.…”
Section: Sarmentosamide (1) Downregulates Jnk and Erk Phosphorylationsupporting
confidence: 79%
“…Cell lysates aliquots were subjected to western blot assay as previously described [3]. Membranes were incubated with specific antibodies against JNK (#9252, Cell Signaling Technology, Beverly, MA, USA), p-JNK (#9251s), ERK (#4695 s), p-ERK (4370 s), p38 (#9212 s), p-p38 (#4511 s), and β-actin (#sc-1616, Santa Cruz Biotechnology, Dallas, TX, USA) in Tris-buffered saline (TBS) buffer containing 5% bovine serum albumin (BSA) and 0.1% Tween-20 at 4 • C overnight.…”
Section: Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides cosmeceutical peptides, there are many other materials with anti-aging and protective functions. Dehydroabietic acid is a natural phytochemical which could improve skin photoaging through the protection and regeneration of collagen fibers in skin [30]. An autologous topical serum based on the plasma rich in growth factors (PRGF) technology has been developed and might counteract the harmful effects of UV radiation [31].…”
Section: Bioactivities Of the Cosmeceutical Peptide Mixturesmentioning
confidence: 99%
“…The optical setup for multi-photon microscopy was as described previously [31]. To visualize collagen fibrils in the dermis of our human skin equivalent, we used second harmonic generation (SHG) imaging (excitation wavelength = 810 nm / emission wavelength = 405/10 nm).…”
Section: Second Harmonic Generation (Shg) Imagingmentioning
confidence: 99%